Evaluating Validity and Reliability of Scientific Literacy Among Indonesian Secondary Students in PISA 2015 Context: Rasch Model Analysis - Saputra, Winata Tegar Saputra; Nuryani Rustaman; Lilit Rusyati (Universitas Negeri Semarang, 2024)
Indonesia has followed the Scientific Literacy Test in PISA OECD and the rank is at the bottom. Scientific literacy is important things in science education because it involves the skills of scientific thinking in society life. This study aims to find the validity and reliability of scientific literacy in PISA 2015 using the Rasch model. The method of this research used quantitative survey research that assessed 15 years of 92 secondary school students. The validity in general shows the test items are not valid, but the validity in each test item shows 17 of 20 questions are valid. Reliability in person is lower than reliability in items. Even though, the test items still have good quality from the reliability findings. The novelty of this study is the validity and reliability of the PISA 2015 test items in Indonesian students as the sample. PISA 2015 used scientific literacy as the dominant test at that time. This study has benefitted other researchers by showing the importance of the validity and reliability of the instruments and ensuring the quality of the instruments for other researchers who will conduct future research using good validity and reliable instruments.